Longitudinal dynamics of body weight change in the development of type 2 diabetes. (25th May 2013) - Hansen, Barbara C.; Newcomb, Jennifer D.; Chen, Ren; Linden, Ellen H.
Abstract : Objective: The aim of this study was to test the obesity–type 2 diabetes mellitus (T2DM) link in the context of longitudinal changes in body weight during the progression to diabetes in mature adult nonhuman primates (NHP). Design and Methods: A colony of 245 adult rhesus monkeys aged 8‐41 years with 179 males were used to define overweight in males as a body weight: ≥13.5 kg or body fat (BF) ≥18% and obesity as ≥16.5 kg or BF ≥27%, and overweight in nonpregnant females was identified as a body weight >8.5 kg or BF >21% and obesity as ≥10.5 kg or BF ≥30%. A subgroup of 48 males (24 T2DM and 24 age‐matched non‐T2DM) males were studied before and following the onset of overt T2DM for the effects of changes in body weight and obesity in inducing this conversion to overt T2DM. Results: Three years before overt T2DM, mean body weight was 18.4 ± 3.3 kg. The DM‐destined group body weight was 3.2 ± 1.1 kg greater and had a longer duration and greater severity of obesity, with peak body weight reached at 3.2 ± 1.8 years before overt T2DM. At DM onset the two groups did not differ significantly in body weight or adiposity. Conclusions: The natural progression from pre‐DM to overt T2DM is caused neither by the amount of excess body weight at DM onset nor by the proximate increases in body weight/adiposity during the pre‐DM period of impaired glucose tolerance. Obesity was, however, essential preceding all NHP cases that developed T2DM.